2014
DOI: 10.1111/cas.12354
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling pathway is a potential therapeutic target for gallbladder cancer

Abstract: Gallbladder cancer (GBC) is a particularly deadly type of cancer with a 5-year survival rate of only 10%. New effective therapeutic strategies are greatly needed. Recently, we have shown that Hedgehog (Hh) signaling is reactivated in various types of cancer and is a potential therapeutic target. However, little is known about the biological significance of Hh signaling in human GBC. In this study, we determined whether Hh signaling could be a therapeutic target in GBC. The Hh transcription factor Gli1 was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
1
47
0
1
Order By: Relevance
“…Gli1 is an effective activator of protein kinase A and itself. Therefore, Gli1 localization within the nucleus is a biomarker of Hh activity (21). Matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, play significant roles in tumor tissue remodeling, and are associated with a number of physiological or pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Gli1 is an effective activator of protein kinase A and itself. Therefore, Gli1 localization within the nucleus is a biomarker of Hh activity (21). Matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, play significant roles in tumor tissue remodeling, and are associated with a number of physiological or pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Once SHH binds to its receptor Patched 1, the transmembrane protein Smoothened is released, causing the transport of the transcription factor glioma-associated oncogene (Gli) into the nucleus, where it regulates the transcription of target genes that control cell differentiation, survival and growth (5,6). Three Gli genes (Gli1, Gli2 and Gli3) have been identified in mammalian tissues, among which Gli1 is considered to be the only loyal marker of hedgehog pathway activity (8)(9)(10) studies have shown that the hedgehog pathway is associated with the migration and invasion of ovarian, pancreatic, esophageal and gastric carcinomas (6,(11)(12)(13). However, to date, the implication of the hedgehog pathway in the aggressiveness of GBM has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that MMP-2 and MMP-9 are mostly associated with migration and invasion in multiple tumor types (14)(15)(16). Further studies have shown that the expression of MMP-2 and MMP-9 in several cancer types is mediated by numerous signaling pathways, which include the hedgehog signaling pathway, the wnt/β-catenin pathway, the phosphoinositide-3 kinase (PI3K)/AKT pathway and the mitogen-activated protein kinase (MAPK) pathway (10,17,18). It has been suggested that the hedgehog signaling pathway is cross-linked with other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression 97% [56], 51.3% [57], 70% [58] Poor prognosis [56,58] [45]. 38.5% [109] Poor prognosis [109] Amplification 9% [45] HER2 (ERRB2) Mutation 9.8% [33] Early event [113] Overexpression 13.8% [110].…”
Section: Name Correlationmentioning
confidence: 99%